Anti-homer-3 Antibody Encephalitis in a 10-Year-Old Child: Case Report and Review of the Literature - Kuang, Zuying; Baizabal-Carvallo, José Fidel; Mofatteh, Mohammad; Xie, Sifen; Wang, Zhanhang; Chen, Yimin (Frontiers in Neurology, 2022)
Objective: We present a rare case with anti-Homer-3 antibodies positive encephalitis in the youngest patient ever identified and reviewed the literature. Case Report: A 10-year-old, Chinese boy came for evaluation of a two-week history of cognitive impairment, irritability, dysarthria and cautious gait. The neurological examination was consistent with a pan-cerebellar syndrome and encephalopathy. CSF was inflammatory with increased leukocytes. Magnetic resonance imaging of the brain showed hyperintensities in both cerebellar hemispheres and vermis in FLAIR and T2- weighted sequences. Infectious disorders were ruled out, but positivity for anti-Homer-3 antibodies was detected in the CSF, but not in the serum. Additionally, low titers of voltage gated calcium channel (VGCC) antibodies were found in the serum. Treatment with intravenous (IV) corticosteroids did not provide meaningful clinical improvement; however, the patient achieved almost complete recovery (modified Ranking Scale score: 1) following IV immunoglobulin. Conclusion: Anti-Homer-3 cerebellar ataxia with encephalopathy should be considered within the differential diagnosis of acute inflammatory cerebellar disease in children and it may coexist with VGCC antibodies.